Analysis Of Thickness And Brightness Of Aluminum Layers In The Anodizing Process With Various Types Of Coloring And Process Times - Farid, Ahmad; Wibowo, Hadi; MK, Imron (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2024)
The coloring process in anodizing can use solutions of inorganic materials or chemical or organic solutions. Chemical solutions produce waste that can be harmful to the environment, therefore it is hoped that there is another alternative, namely by using dyes produced from leaves, or from fruit, or from tubers, such as purple cassava, carrots or others. Of course, these natural ingredients are easy to obtain, cheap and environmentally friendly. The problem raised in this research is the results of the thickness and brightness of the surface of aluminum metal which is processed by anodizing using various types of coloring from using special coloring materials, food coloring, dragon fruit and pandan leaves. Thus, the aim of the research carried out is to be able to find out from the initial process of anodizing coloring to analyzing the final results of thickness and brightness obtained to be able to conclude which type of coloring is better apart from the special dyes that exist as an alternative to using natural coloring materials.This research method uses an experimental method where the experimental or experimental method uses various types of dyes, namely special dyes (non-natural) and natural dyes (food coloring, dragon fruit extract and purple sweet potato) which are tested with variations in anodizing time of 10, 20 and 30 minutes.The research results showed that to make coloring on aluminum metal using the anodizing process, the following steps are required: etching→ rinse→ desmutting→ rinse→ doff→ rinse→ desmuting→ rinse→ anodizing→ rinse→ coloring→ rinse→ sealing→ rinse→ finish. In coloring tests on aluminum metal using the anodizing process, varying the type of coloring and the length of time for the anodizing process of 10, 20 and 30 minutes, the average thickness for the special dye (orange) was 0.033mm, the natural dye from tubers (purple) was 0.027mm, food coloring (red) 0.023mm, and from pandan leaves (green) 0.016mm. So it can be concluded that the thick type of coloring is from special dyes and the thick coloring below is from natural dyes, namely from purple sweet potatoes, then food coloring and the thinnest is from pandan leaf coloring. As for the analysis of the evenness of the coloring, data was also obtained, namely with special dyes, while the ones that were uneven were purple sweet potatoes.